Calculation of spin-spin zero-field splitting within periodic boundary conditions: Towards all-electron accuracy - Biktagirov, Timur; Schmidt, Wolf Gero; Gerstmann, Uwe (Physical Review B)

Vibrational properties of the Au-(3×3)/Si(111) surface reconstruction - Halbig, B.; Liebhaber, M.; Bass, U.; Geurts, J.; Speiser, E.; Räthel, J.; Chandola, S.; Esser, N.; Krenz, Marvin; Neufeld, Sergej; Schmidt, Wolf Gero; Sanna, S. (Physical Review B)

Probing quasi-one-dimensional band structures by plasmon spectroscopy - Lichtenstein, T.; Mamiyev, Z.; Braun, Christian; Sanna, S.; Schmidt, Wolf Gero; Tegenkamp, C.; Pfnür, H. (Physical Review B)

Microscopic theory of cavity-enhanced single-photon emission from optical two-photon Raman processes - Breddermann, Dominik; Praschan, Tom; Heinze, Dirk Florian; Binder, Rolf; Schumacher, Stefan (Physical Review B)

Polytypism driven zero-field splitting of silicon vacancies in 6H-SiC - Biktagirov, Timur; Schmidt, Wolf Gero; Gerstmann, Uwe; Yavkin, Boris; Orlinskii, Sergei; Baranov, Pavel; Dyakonov, Vladimir; Soltamov, Victor (Physical Review B)

Spin pairing versus spin chains at Si(553)-Au surfaces - Braun, Christian; Gerstmann, Uwe; Schmidt, Wolf Gero (Physical Review B)

Metal-insulator transition in the dimerized organic conductor κ−(BEDT-TTF)2Hg(SCN)2Br - Ivek, Tomislav; Beyer, Rebecca; Badalov, Sabuhi; Čulo, Matija; Tomić, Silvia; Schlueter, John A.; Zhilyaeva, Elena I.; Lyubovskaya, Rimma N.; Dressel, Martin (Physical Review B)

Spin dynamics of quadrupole nuclei in InGaAs quantum dots - Kuznetsova, M. S.; Cherbunin, R. V.; Gerlovin, I. Ya.; Ignatiev, I. V.; Verbin, S. Yu.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Photon echoes from (In,Ga)As quantum dots embedded in a Tamm-plasmon microcavity - Salewski, M.; Poltavtsev, S. V.; Kapitonov, Yu. V.; Vondran, J.; Yakovlev, D. R.; Schneider, C.; Kamp, M.; Höfling, S.; Oulton, R.; Akimov, I. A.; Kavokin, A. V.; Bayer, M. (Physical Review B)
We report on the coherent optical response from an ensemble of (In,Ga)As quantum dots (QDs) embedded in a planar Tamm-plasmon microcavity with a quality factor of approximately 100. Significant enhancement of the light-matter interaction is demonstrated under selective laser excitation of those quantum dots which are in resonance with the cavity mode. The enhancement is manifested through Rabi oscillations of the photon echo, demonstrating coherent control of excitons with picosecond pulses at intensity levels more than an order of magnitude smaller as compared with bare quantum dots. The decay of the photon echo transients is weakly changed by the resonator, indicating a small decrease of the coherence time T2 which we attribute to the interaction with the electron plasma in the metal layer located close (40 nm) to the QD layer. Simultaneously we see a reduction of the population lifetime T1, inferred from the stimulated photon echo, due to an enhancement of the spontaneous emission by a factor of 2, which is attributed to the Purcell effect, while nonradiative processes are negligible, as confirmed from time-resolved photoluminescence.

Double resonant plasmonic nanoantennas for efficient second harmonic generation in zinc oxide - Weber, Nils; Protte, Maximilian; Walter, Felicitas; Georgi, Philip; Zentgraf, Thomas; Meier, Cedrik (Physical Review B)

Solving the Bethe-Salpeter equation for the second-harmonic generation in Zn chalcogenides - Riefer, A.; Schmidt, Wolf Gero (Physical Review B)

Understanding band alignments in semiconductor heterostructures: Composition dependence and type-I–type-II transition of natural band offsets in nonpolar zinc-blendeAlxGa1−xN/AlyGa1−yNcomposites - Landmann, M.; Rauls, E.; Schmidt, Wolf Gero (Physical Review B)

Electron paramagnetic resonance calculations for hydrogenated Si surfaces - Rohrmüller, M.; Schmidt, Wolf Gero; Gerstmann, Uwe (Physical Review B)

Tuning the conductivity along atomic chains by selective chemisorption - Edler, F.; Miccoli, I.; Stöckmann, J. P.; Pfnür, H.; Braun, Christian; Neufeld, Sergej; Sanna, S.; Schmidt, Wolf Gero; Tegenkamp, C. (Physical Review B)

Understanding band alignments in semiconductor heterostructures: Composition dependence and type-I–type-II transition of natural band offsets in nonpolar zinc-blendeAlxGa1−xN/AlyGa1−yNcomposites - Landmann, M.; Rauls, E.; Schmidt, Wolf Gero (Physical Review B)

Vortex-vortex control in exciton-polariton condensates - Ma, Xuekai; Schumacher, Stefan (Physical Review B)

Anisotropic excitons and their contributions to shift current transients in bulk GaAs - Podzimski, Reinold; Duc, Huynh Thanh; Meier, Torsten (Physical Review B)

Time-resolved photon echoes from donor-bound excitons in ZnO epitaxial layers - Poltavtsev, S. V.; Kosarev, A. N.; Akimov, I. A.; Yakovlev, D. R.; Sadofev, S.; Puls, J.; Hoffmann, S. P.; Albert, M.; Meier, Cedrik; Meier, Torsten; Bayer, M. (Physical Review B)

Damping of Rabi oscillations in intensity-dependent photon echoes from exciton complexes in a CdTe/(Cd,Mg)Te single quantum well - Poltavtsev, S. V.; Reichelt, Matthias; Akimov, I. A.; Karczewski, G.; Wiater, M.; Wojtowicz, T.; Yakovlev, D. R.; Meier, Torsten; Bayer, M. (Physical Review B)

All-optical tailoring of single-photon spectra in a quantum-dot microcavity system - Breddermann, D.; Heinze, Dirk Florian; Binder, R.; Zrenner, Artur; Schumacher, Stefan (Physical Review B)

Electron spin dynamics in cubic GaN - Buß, J. H.; Schupp, T.; As, Donat Josef; Brandt, O.; Hägele, D.; Rudolph, J. (Physical Review B)

Stabilizing nuclear spins around semiconductor electrons via the interplay of optical coherent population trapping and dynamic nuclear polarization - Onur, A. R.; de Jong, J. P.; O'Shea, D.; Reuter, Dirk; Wieck, A. D.; van der Wal, C. H. (Physical Review B)

Reconstruction of nuclear quadrupole interaction in (In,Ga)As/GaAs quantum dots observed by transmission electron microscopy - Sokolov, P. S.; Petrov, M. Yu.; Mehrtens, T.; Müller-Caspary, K.; Rosenauer, A.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

All-optical tailoring of single-photon spectra in a quantum-dot microcavity system - Breddermann, D.; Heinze, D.; Binder, R.; Zrenner, Artur; Schumacher, Stefan (Physical Review B)
Semiconductor quantum-dot cavity systems are promising sources for solid-state-based on-demand generation of single photons for quantum communication. Commonly, the spectral characteristics of the emitted single photon are fixed by system properties such as electronic transition energies and spectral properties of the cavity. In the present work we study cavity-enhanced single-photon generation from the quantum-dot biexciton through a partly stimulated nondegenerate two-photon emission. We show that frequency and linewidth of the single photon can be fully controlled by the stimulating laser pulse, ultimately allowing for efficient all-optical spectral shaping of the single photon.

Existence of topological nontrivial surface states in strained transition metals: W, Ta, Mo, and Nb - Thonig, Danny; Rauch, Tomáš; Mirhosseini, Hossein; Henk, Jürgen; Mertig, Ingrid; Wortelen, Henry; Engelkamp, Bernd; Schmidt, Anke B.; Donath, Markus (Physical Review B)

Orbital-symmetry-selective spin characterization of Dirac-cone-like state on W(110) - Miyamoto, K.; Wortelen, H.; Mirhosseini, Hossein; Okuda, T.; Kimura, A.; Iwasawa, H.; Shimada, K.; Henk, J.; Donath, M. (Physical Review B)

Experimental realization of a polariton beam amplifier - Niemietz, Dominik; Schmutzler, Johannes; Lewandowski, Przemyslaw; Winkler, Karol; Aßmann, Marc; Schumacher, Stefan; Brodbeck, Sebastian; Kamp, Martin; Schneider, Christian; Höfling, Sven; Bayer, Manfred (Physical Review B)

Dynamics of exciton-polaritons in discrete lattices under incoherent localized pumping - Yulin, A. V.; Chestnov, I. Yu.; Ma, X.; Schumacher, Stefan; Peschel, U.; Egorov, O. A. (Physical Review B)

Polarization dependence of nonlinear wave mixing of spinor polaritons in semiconductor microcavities - Lewandowski, Przemyslaw; Lafont, Ombline; Baudin, Emmanuel; Chan, Chris K. P.; Leung, P. T.; Luk, Samuel M. H.; Galopin, Elisabeth; Lemaître, Aristide; Bloch, Jacqueline; Tignon, Jerome; Roussignol, Philippe; Kwong, N. H.; et al. (Physical Review B)

Vibration eigenmodes of the Au-(5×2)/Si(111) surface studied by Raman spectroscopy and first-principles calculations - Liebhaber, M.; Halbig, B.; Bass, U.; Geurts, J.; Neufeld, Sergej; Sanna, S.; Schmidt, Wolf Gero; Speiser, E.; Räthel, J.; Chandola, S.; Esser, N. (Physical Review B)

LiNbO3 electronic structure: Many-body interactions, spin-orbit coupling, and thermal effects - Riefer, Arthur; Friedrich, Michael; Sanna, Simone; Gerstmann, Uwe; Schindlmayr, Arno; Schmidt, Wolf Gero (Physical Review B)
The influence of electronic many-body interactions, spin-orbit coupling, and thermal lattice vibrations on the electronic structure of lithium niobate is calculated from first principles. Self-energy calculations in the GW approximation show that the inclusion of self-consistency in the Green function G and the screened Coulomb potential W opens the band gap far stronger than found in previous G0W0 calculations but slightly overestimates its actual value due to the neglect of excitonic effects in W. A realistic frozen-lattice band gap of about 5.9 eV is obtained by combining hybrid density functional theory with the QSGW0 scheme. The renormalization of the band gap due to electron-phonon coupling, derived here using molecular dynamics as well as density functional perturbation theory, reduces this value by about 0.5 eV at room temperature. Spin-orbit coupling does not noticeably modify the fundamental gap but gives rise to a Rashba-like spin texture in the conduction band.

Strain-induced quasi-one-dimensional rare-earth silicide structures on Si(111) - Timmer, F.; Oelke, R.; Dues, C.; Sanna, S.; Schmidt, Wolf Gero; Franz, M.; Appelfeller, S.; Dähne, M.; Wollschläger, J. (Physical Review B)

Surface vibrational Raman modes of In:Si(111)(4×1)and(8×2)nanowires - Speiser, E.; Esser, N.; Wippermann, S.; Schmidt, Wolf Gero (Physical Review B)

Grand canonical Peierls transition in In/Si(111) - Jeckelmann, Eric; Sanna, Simone; Schmidt, Wolf Gero; Speiser, Eugen; Esser, Norbert (Physical Review B)

Rare-earth silicide thin films on the Si(111) surface - Sanna, S.; Dues, C.; Schmidt, Wolf Gero; Timmer, F.; Wollschläger, J.; Franz, M.; Appelfeller, S.; Dähne, M. (Physical Review B)

Atomic size effects studied by transport in single silicide nanowires - Miccoli, I.; Edler, F.; Pfnür, H.; Appelfeller, S.; Dähne, M.; Holtgrewe, K.; Sanna, S.; Schmidt, Wolf Gero; Tegenkamp, C. (Physical Review B)

Collective state transitions of exciton-polaritons loaded into a periodic potential - Winkler, K.; Egorov, O. A.; Savenko, I. G.; Ma, Xuekai; Estrecho, E.; Gao, T.; Müller, S.; Kamp, M.; Liew, T. C. H.; Ostrovskaya, E. A.; Höfling, S.; Schneider, C. (Physical Review B)

Dynamics of exciton-polaritons in discrete lattices under incoherent localized pumping - Yulin, A. V.; Chestnov, I. Yu.; Ma, Xuekai; Schumacher, S.; Peschel, U.; Egorov, O. A. (Physical Review B)

Incoherent control of topological charges in nonequilibrium polariton condensates - Ma, Xuekai; Peschel, Ulf; Egorov, Oleg A. (Physical Review B)

Ultrafast shift and rectification photocurrents in GaAs quantum wells: Excitation intensity dependence and the importance of band mixing - Duc, Huynh Thanh; Podzimski, Reinold; Priyadarshi, Shekhar; Bieler, Mark; Meier, Torsten (Physical Review B)
A microscopic approach that is based on the multisubband semiconductor Bloch equations formulated in the basis of a 14-band k⋅p model is employed to compute the temporal dynamics of photocurrents in GaAs quantum wells following excitation with femtosecond laser pulses. This approach provides a transparent description of the interband, intersubband, and intraband excitations, fully includes all resonant as well as off-resonant excitations, and treats the light-matter interaction nonperturbatively. For linearly polarized excitations, the photocurrents contain contributions from shift and rectification currents. We numerically compute and analyze these currents generated by excitation with femtosecond laser pulses for [110]- and [111]-oriented GaAs quantum wells. It is shown that the often employed perturbative χ(2) approach breaks down for peak fields larger than about 10 kV/cm, and that nonperturbative effects lead to a reduction of the peak values of the shift and rectification currents and to temporal oscillations that originate from Rabi flopping. In particular, we find a complex oscillatory photon energy dependence of the magnitudes of the shift and rectification currents. Our simulations demonstrate that this dependence is the result of mixing between the heavy- and light-hole valence bands. This is a surprising finding since the band mixing has an even larger influence on the strength of the photocurrents than the absorption coefficient. For [110]-oriented GaAs quantum wells, the calculated photon energy dependence is compared to experimental results, and good agreement is obtained. This validates our theoretical approach.

Ultrafast dynamical response of the lower exciton-polariton branch in CdZnTe - Lohrenz, J.; Melzer, S.; Ruppert, C.; Akimov, I. A.; Mariette, H.; Reichelt, Matthias; Trautmann, Alexander; Meier, Torsten; Betz, M. (Physical Review B)
We investigate the transient optical response in high-quality Cd0.88Zn0.12Te crystals in the regime of slow light propagation on the lower exciton-polariton branch. Femtosecond photoexcitation leads to very substantial transmission changes in a ∼10-meV broad spectral range within the transparency window of the unexcited semiconductor. These nonlinear optical signatures decay on picosecond time scales governed by carrier thermalization and recombination. The temporal and spectral dependence indicate the dynamical optical response as arising from excitation-induced dephasing and perturbed free induction decay. Model simulations for the optical response taking into account the actual exciton-polariton dispersion and excitation-induced dephasing of a nonlinearly driven two-level system support this interpretation.

Vibrational properties of LiNb1−xTaxO3 mixed crystals - Rüsing, Michael; Sanna, Simone; Neufeld, Sergej; Berth, Gerhard; Schmidt, Wolf Gero; Zrenner, Artur; Yu, H.; Wang, Y.; Zhang, H. (Physical Review B)
Congruent lithium niobate and lithium tantalate mixed crystals have been grown over the complete compositional range with the Czochralski method. The structural and vibrational properties of the mixed crystals are studied extensively by x-ray diffraction measurements, Raman spectroscopy, and density functional theory. The measured lattice parameters and vibrational frequencies are in good agreement with our theoretical predictions. The observed dependence of the Raman frequencies on the crystal composition is discussed on the basis of the calculated phonon displacement patterns. The phononic contribution to the static dielectric tensor is calculated by means of the generalized Lyddane-Sachs-Teller relation. Due to the pronounced dependence of the optical response on the Ta concentration, lithium niobate tantalate mixed crystals represent a perfect model system to study the properties of uniaxial mixed ferroelectric materials for application in integrated optics.